Strategic approaches to tourism development in village destinations for increased competitiveness and sustainability - Ni Made Karunia Noina; Ni Made Eka Mahadewi; I Ketut Surata (Universitas Merdeka Malang, 2024)
Tourism has become a significant driver of global economic dynamics, including in Indonesia. This sector acts as a catalyst for economic growth through job creation, foreign exchange earnings, and the revitalization of local culture. However, like other sectors, tourism faces challenges that require adaptation. The COVID-19 pandemic was one of the biggest challenges, causing prolonged stagnation, the closure of tourist destinations, and a drastic decline in tourist numbers. Post-pandemic, there has been a strong push not only to recover tourism but also to reconstruct it with more sustainable and resilient approaches. In Indonesia, there is growing attention towards sustainable tourism development, in line with global commitments to the Sustainable Development Goals (SDGs). One notable example is the development of tourist villages that not only rely on natural and cultural attractions but also emphasize local community empowerment, environmental preservation, and cultural heritage protection. This study focuses on Desa Wisata Antap, a tourism village in Bali with considerable potential that has yet to be optimally utilized. The research aims to identify internal and external conditions affecting the sustainability of tourism in Desa Wisata Antap and provide strategic alternatives for sustainable tourism development. A qualitative approach using SWOT analysis was employed to explore existing conditions, identifying strengths, weaknesses, opportunities, and threats. The findings highlight the importance of active stakeholder involvement and the need for integrated management strategies that balance economic, social, and environmental sustainability. The proposed strategies emphasize collaboration, digital marketing, and capacity building to ensure the long-term sustainability of the destination.